Alcohol and other drug (AOD) staffing and their workplace: examining the relationship between clinician and organisational workforce characteristics and treatment outcomes in the AOD field. (2nd January 2020) - van de Ven, Katinka; Ritter, Alison; Roche, Ann
Abstract: While there is a long-standing and commonly held belief that the characteristics of the alcohol and other drug (AOD) workforce and workplace can impact client treatment outcomes, the available literature has not been systematically reviewed to date. Knowing which characteristics may impact treatment outcomes can help maximise workforce development in AOD services. A systematic review was undertaken, to identify studies of five clinician and organisational workforce characteristics: (1) years of clinical experience; (2) level of education/qualifications; (3) staff turnover; (4) staff-to-client ratio; and (5) professional development, and their relationship to client treatment outcome. Each study was assessed for quality using the Cochrane risk of bias tool. The search identified 1317 records; only 12 studies directly examined the relationship between clinician and organisational workforce characteristics and AOD treatment outcomes. Our analysis revealed a limited number of studies, a lack of high-quality research, and highly variable evidence regarding the relationship between clinician and organisational characteristics, and treatment outcomes. At present, there is an absence of evidence to support a strong association in any direction. Importantly, these findings illustrate the need for higher quality and larger scale research that focuses on clinician and organisational characteristics, taking into account multiple intervening and mediating factors.